Proposition of a New Severity Analysis Based on 'Shake' Detection: Example of the Vatry Airport Tarmac. (26th November 2014) - Huart, Victor; Candore, Jean‐Charles; Nolot, Jean‐Baptiste; Krajka, Nicolas; Pellot, Jérôme; Odof, Serge; Erre, Damien
<x xml:space="preserve">Abstract</x> In packaging science, the study of transport is important in determining the viability of a package/product pair. Many load breaks occur (e.g. handling and storage) along a supply chain. Transport also generates various physical stresses (e.g. shocks, shakes and vibrations). These physical phenomena can be recorded using a variety of customized sensors (e.g. tri‐axial accelerometers, temperature sensors and pressure sensors). This study focuses on a transport phase that has not been studied in depth to date. Transportation operations on tarmacs include many handling and transportation machines, which are characterized by typical constraints that are often more stringent than airlift phase constraints. For comparison, acceleration distributions were estimated and analysed for the tarmac phase and road phase. Severity indicators were calculated based on existing methods. The second part of this study addresses the study of shakes. The shake distributions at 90 and 95% were another indicator of the shakes' severity and probability of occurrence. These elements allow us to characterize the impact of the tarmac area during air transport.